Practicality of E-Modules Based on Problem-Based Learning (PBL) Learning Model on Digestive System Material - Ibrahim, Mohammad Andre; Latjompoh, Masra; Abdul, Aryati; Ibrahim, Mustamin; Solang, Margaretha; Akbar, Muh. Nuh (Universitas Labuhanbatu, 2023)
Electronic modules are electronic learning media that are systematically arranged and include competencies that will be mastered by students and are equipped with an attractive appearance. Problem-based learning is a learning strategy that focuses on improving students' ability to learn and collaborate in groups to find solutions to problems in the surrounding environment. This study aims to describe the implementation of learning and student activities using e-modules based on problem-based learning of digestive system material. This study used the research and development (R&D) method modified by Sugiyono (2017). Data collection techniques used observation sheets of learning implementation and student activity sheets. The problem-based learning e-module trial was conducted on a limited scale. The subjects in this study were 15 students of Class XI 1 SMA Negeri 1 Tapa. The results of the study found that the practicality test based on the percentage of learning implementation was 88.7% in the